2013
DOI: 10.1089/ten.tea.2012.0646
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Donor Variation and Senescence on Endothelial Differentiation of Human Mesenchymal Stromal Cells

Abstract: Tissue Engineering Part A The effect of donor variation and senescence on endothelial differentiation of human mesenchymal stromal cells (doi: 10.1089(doi: 10. /ten.TEA.2012 This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…72,75 Recently several groups have focused on differentiation of MSCs into endothelial cells, an approach that has potential to be useful in direct transplant into anti-angiogenic environments such as ischemic wound beds. Results have shown endothelial-like cell populations derived from human MSCs in vitro with varying degrees of donor variation, 76,77 while Bago et al showed similar results for amnion-derived MSCs in glioma tumors. 78 Furthermore, pericytes that stabilize vessel walls and promote vessel maturation during angiogenesis have been shown to be derived from bone marrow populations following injury.…”
Section: Stimulation Of Angiogenesismentioning
confidence: 95%
“…72,75 Recently several groups have focused on differentiation of MSCs into endothelial cells, an approach that has potential to be useful in direct transplant into anti-angiogenic environments such as ischemic wound beds. Results have shown endothelial-like cell populations derived from human MSCs in vitro with varying degrees of donor variation, 76,77 while Bago et al showed similar results for amnion-derived MSCs in glioma tumors. 78 Furthermore, pericytes that stabilize vessel walls and promote vessel maturation during angiogenesis have been shown to be derived from bone marrow populations following injury.…”
Section: Stimulation Of Angiogenesismentioning
confidence: 95%
“…hMSCs were expanded up to passage 2 and used in passage 3 to test their differentiation potential. The determination of cell surface marker expression (CD105, CD11b, CD19, CD45, HLA-DR, CD90, CD73, CD34), osteogenic potential, adipogenic potential, and endothelial induction of the used hMSC donors is described elsewhere [22,23].…”
Section: Cell Expansion and Differentiationmentioning
confidence: 99%
“…Changes in upstream regulators and biofunctions were visualized using Ingenuity Pathway Analysis software (IPA Ò ; Ingenuity Systems). In this study, the described data set was previously used by Portalska et al and Mentink et al [22,23]. We reanalyzed this data set after the formation of two groups: good and low chondrogenic performing hMSC donors.…”
Section: Microarray Expression Profilingmentioning
confidence: 99%
See 2 more Smart Citations